Analysis of the expression of matrix RNA of a panel of genes of morphologically unchanged rectal epithelium as a method of early diagnosis of colon pathology - V. C. Bozhenko; S. V. Goncharov; M. V. Zakharenko; Ya. Yu. Kiseleva; T. A. Karmakova; T. M. Kulinich; U. S. Stanoevich; N. V. Melnikova; A. L. Senchukova; I. B. Grunin; O. P. Bliznyukov; V. A. Solodky (Успехи молекулярной онкологии, 2023)
Introduction. The absence of specific clinical symptoms in the early stages of colorectal cancer development leads to the fact that a quarter of patients who seek help for the first time have a metastatic stage of the disease. For the timely detection of pre-tumor disorders or hidden foci of malignancy, the possibilities of modern molecular biological technologies are being actively studied today.Aim. To develop a method for diagnosing tumor diseases of the colon based on molecular genetic analysis of morphologically unchanged intestinal epithelium distant from the focus of the tumor lesion.Materials and methods. We examined the matrix RNA (mRNA)  expression profile of 63 candidate genes potentially associated with the pathogenesis of neoplastic changes in rectal mucosal samples. Samples were obtained during prophylactic and/or diagnostic video colonoscopy of 122 patients, 41 of whom had no history of breast cancer (“Normal”), 32 patients were diagnosed with breast cancer polyps (“Polyposis”) and 49 patients were diagnosed with breast cancer (“colorectal cancer”). mRNA expression was assessed by reverse transcription polymerase chain reaction.Results. Using the discriminant analysis method, it was established that  the cellular material of scrapings from the rectum in the “colorectal cancer” group reliably, with a classification accuracy above 96 %, differs in expression phenotype from the “Normal” and “Polyposis” groups.Conclusion. The data obtained are a prerequisite for the development of a minimally invasive diagnostic method that can be used as part of an outpatient  examination to assess the risk of colon tumor disease.